Acquisition of the verb movement parameter in English by adult Arabic speakers - Ali Muftah, Muneera Yahya; Wong, Bee Eng (Universiti Putra Malaysia Press, 2014)
This study investigates the acquisition of the verb movement parameter in English by adult Arabic-speaking learners of English as a Second Language (ESL) 1 . English and Arabic differ in the settings they adopt for the verb movement parameter. English is [-strong], while Arabic is [+strong]. Accordingly, the placement of the verb with respect to negation, adverbs and floating quantifiers (FQs) in English are considered difficult to acquire for adult Arabic ESL learners. In order to examine the nature of adult Arabic ESL learners’ interlanguage (IL) grammar at the L2 ultimate attainment level as well as the extent to which the adult Arabic ESL learners can reset the verb movement parameter and correctly place the verb with respect to negation, adverbs and FQs in finite and non-finite contexts with lexical and auxiliary verbs, an oral production task was conducted with 77 adult Arabic ESL learners who were subdivided into three proficiency levels (lower-intermediate, upper-intermediate and advanced). The results reveal that the Arabic ESL learners, even at ultimate attainment level, have great difficulty in resetting the parameterized property associated with the verb movement. These results support the Failed Functional Features Hypothesis (FFFH) (Hawkins and Chan, 1997) which proposes that post-childhood adult L2 learners are unable to reset parameters from their L1 values to the L2 settings where these differ from the L1 settings